(untitled) (Global Journal of Human-Social Science, 2020)
This work is part of a broader research that investigates what the social representations of psychology professionals who work in the Centros de Referência de Assistência Social (CRAS) are about the users of this service that make up the Sistema Único de Assistência Social (SUAS) in Brazil. With the study, it was sought to deeply understand the conceptions built and shared about the users. As a method, open interviews were used, with a reference guide topic. In total, 21 psychologists were interviewed, in 20 different CRAS from 14 municipalities in the metropolitan and central region of Rio Grande do Sul, Brazil. Participants were gathered for convenience. The transcribed material was submitted to discourse analysis. Among the results of the research, meanings referring to the social representation of vulnerability appear, presented here, which strongly characterizes the users of CRAS/SUAS in the view of the interviewees, especially regarding the situation of poverty and other violations of rights basic human beings associated with this, revealing the multiple character of vulnerability, which demarcates its own space and also certain forms of relationship of the population in this life situation.